Ajax for web application developers - Hadlock, Kris (Developer's library., 2006)
Reusable components and patterns for Ajax-driven applications Ajax is one of the latest and greatest ways to improve users' online experience and create new and innovative web functionality. By allowing specific parts of a web page to be displayed without refreshing the entire page, Ajax significantly enhances the experience of web applications. It also lets web developers create intuitive and innovative interaction processes. Ajax for Web Application Developers provides the in-depth working knowledge of Ajax that web developers need to take their web applications to the next level. The book shows how to create an Ajax-driven web application from an object-oriented perspective, and it includes discussion of several useful Ajax design patterns. This detailed guide covers the creation of connections to a MySQL database with PHP 5 via a custom Ajax engine and shows how to gracefully format the response with CSS, JavaScript, and XHTML while keeping the data tightly secure. It also covers the use of four custom Ajax-enabled components in an application and how to create each of them from scratch. The final section of the book combines the individual code examples and techniques from earlier chapters of the book into one larger, Ajax-driven application-an internal web mail application that can be used in any user-based application, such as a community-based web application. Readers will learn not only how to create and use their own reusable Ajax components in this application but also how to connect their components to any future Ajax applications that they might build. Web Development/Ajax/JavaScript.